Assessment of heat-killed E. coli expressing Chikungunya virus E2 protein as a candidate vaccine for dual protection against Chikungunya virus and E. coli - Patra, Surajit; Gajbhiye, Virendra; Karpe, Yogesh A. (Frontiers in Immunology, 2025)
The Chikungunya virus (CHIKV) is a mosquito-borne virus with a long history of recurring epidemics transmitted through Aedes mosquitoes. The rapid spread of CHIKV has intensified the need for potent vaccines. Escherichia coli (E.coli), a vital part of human gut microbiota, is utilized in recombinant DNA technology for cloning. However, its high adaptability can lead to severe infections in humans. This study aimed to develop the candidate dual vaccine against CHIKV and E. coli. For this, we expressed the CHIKV E2 protein in the E. coli Rosetta Bl21 cells and the protein expression was confirmed by western blotting. The IgG immune response of the candidate vaccine was determined against CHIKV and E. coli by ELISA. Further, the potential of antibodies to neutralize CHIKV was evaluated via Tissue Culture Infectious Dose 50 (TCID50). We observed that cells expressing E2 protein with alum immunized mice serum showed a five-fold higher IgG immune response against CHIKV, compared to control cells. The CHIKV neutralization assay results showed a two-fold decrease in CHIKV TCID50 value after 12 hours and a three-fold reduction after 120 hours. Similarly, the vaccine formulation also elicited a significantly higher IgG immune response against E. coli. The results suggested that expressing CHIKV E2 protein in E. coli is a potential approach for generating an IgG immune response against CHIKV and E. coli both. This study proposes a faster, safer, and cost-effective recombinant protein-based vaccine development.